2019
DOI: 10.1155/2019/3958908
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Expression in Human Breast Cancer Stem Cells Is Epigenetically Regulated through Posttranslational Histone Modifications

Abstract: Tumor progression through immune evasion is a major challenge in cancer therapy. Recent studies revealed that enhanced PD-L1 expression in cancer stem cells is linked to immune evasion. Understanding the mechanisms behind this PD-L1 overexpression in cancer stem cells is critical for developing more effective strategies for preventing immune evasion and increasing the efficacy of anti-PD-1/PD-L1 therapy. Tumorsphere formation in breast cancer cells enhanced epithelial to mesenchymal transition (EMT), which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 39 publications
1
43
0
1
Order By: Relevance
“…In the present study, higher expression of PD-L1 was observed in the CSC population of the CSC culture compared with the CSC population of the WP culture. These results were supported by previous studies, in which PD-L1 expression was positively associated with the expression of stemness markers (20,21), and supported the notion that BCA55-121-CSC cultures possessed CSC properties. In the present study, CSC RNA could be presented as tumor antigens by DCs and activated T cells in the whole T cell population and enriched CD8 + T cells, to stimulate an enhanced ability to kill cancer cells superior to that obtained using RNA from the total BCA55-121 cell population.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, higher expression of PD-L1 was observed in the CSC population of the CSC culture compared with the CSC population of the WP culture. These results were supported by previous studies, in which PD-L1 expression was positively associated with the expression of stemness markers (20,21), and supported the notion that BCA55-121-CSC cultures possessed CSC properties. In the present study, CSC RNA could be presented as tumor antigens by DCs and activated T cells in the whole T cell population and enriched CD8 + T cells, to stimulate an enhanced ability to kill cancer cells superior to that obtained using RNA from the total BCA55-121 cell population.…”
Section: Discussionsupporting
confidence: 87%
“…The present study revealed that CSCs were more resistant compared with the whole cancer cell population to effector T cells. This may be explained by the finding that the CSC population in CSC cultures expressed high levels of PD-L1 (20), which may induce apoptosis of effector T cells (31). These in vitro findings need to be investigated in an ex vivo system and in clinical trials for the development of DC-based activation of T cells against breast CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Histone H3 acetylation of the PD-L1 promoter is increased and mediated by the c-Jun/HDAC3 axis in drugresistant A549/CDDP, MCF7/ADR and HepG2/ADR cells Epigenetic modifications, such as DNA methylation and histone acetylation, are frequently involved in regulating PD-L1 expression in cancer cells [23][24][25]. First, a total of 18 CpG islands in the PD-L1 promoter region were sequenced, and the DNA methylation of the PD-L1 promoter region was barely changed in the drug-resistant cancer cells in our study (Additional file 1: Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence demonstrates that epigenetic modifications such as DNA methylation and histone acetylation are frequently involved in PD-L1 expression in cancer cells [23,25]. Methylation of CpG islands over the PD-L1 promoter region negatively regulates PD-L1 transcription [39].…”
Section: Discussionmentioning
confidence: 99%
“…Mathematical model-based analysis can also be used to comment on the possibility of tumor initiation within a clinically observable time with respect to the presence of BCSCs [28]. Here, we note that the high levels of PD-1/PD-L1 expression reported on CSCs are believed to aid immune evasion [180,181]. The expression of PD-L1 in BCSC is linked to enhancing the presence of transcription factors such as OCT-4A and Nanog [180].…”
Section: Mathematical Models Used For Breast Cancer Managementmentioning
confidence: 95%